1990
DOI: 10.1002/ar.1092260309
|View full text |Cite
|
Sign up to set email alerts
|

Remission of the polycystic ovarian condition (PCO) in the rat following hemiovariectomy

Abstract: The estradiol valerate-induced polycystic ovarian condition in the rat represents a normal ovarian response to aberrant endocrine stimuli. Although we have shown that removal of one polycystic ovary (hemiovariectomy) results in restoration of cyclicity and normal morphology in the remaining ovary by 1 week, nothing is known about the process of recovery or about the role of the hypothalamo-pituitary unit in initiating recovery. We have therefore examined ovaries at 3, 12, 24, 48, and 120 hours following remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
(27 reference statements)
5
16
1
Order By: Relevance
“…In studies on EV-and E 2 -treated rats also, corpora lutea were not found [11,14]. In the present experiments on guinea pigs, few corpora lutea were found in the overtly cystic condition.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In studies on EV-and E 2 -treated rats also, corpora lutea were not found [11,14]. In the present experiments on guinea pigs, few corpora lutea were found in the overtly cystic condition.…”
Section: Discussioncontrasting
confidence: 67%
“…EV-and E 2 -treated rats exhibit cysts that resemble the human condition [11,14]. The situation in guinea pigs is also similar to that in both humans and rats.…”
Section: Discussionsupporting
confidence: 59%
“…Due to this intermediate status, some studies have postulated that this type of follicle (those that still possess oocytes) intensely binds hCG (Brawer et al 1989) and can be rescued from this status and be ovulated (Brawer et al 1989, Convery et al 1990). Therefore, it is possible that type III follicles originate from the antral preovulatory follicles.…”
Section: Kp and Ovulationmentioning
confidence: 99%
“…The follicles were counted and classified as healthy or atretic (Brawer et al 1986, Convery et al 1990. Preantral follicles were defined as follicles without any antral cavity and with two or more layers of granulosa cells.…”
Section: Study Proceduresmentioning
confidence: 99%